Cholesteric Liquid Crystals Sensors Based on Nanocellulose Derivatives for Improvement of Quality of Human Life: A Review - Arnaldo Leal‐Junior; Maria Simone Soares; Pedro Marques deAlmeida; Carlos Marques (Advanced Sensor Research, 2023)
Abstract This paper presents a review of cholesteric liquid crystal (CLC) sensors based on water and hydroxypropyl cellulose (HPC) mixtures for healthcare and human quality of life applications. First, an overview of the sensors system demands for healthcare and environmental sensing is presented in which there is also a discussion on the sensors technologies conventionally applied in these scenarios. Then, a discussion of the water‐HPC mixtures and the formation of the CLCs as well as their operation principle and fabrication methods is presented. Thereafter, the applications of such technologies for the assessment of different parameters related to biomechanics, medical conditions, and environment contamination are discussed in detail. Thus, the use of CLC sensors based on HPC membranes provides novel sustainable approaches for highly sensitive sensors systems with intuitive signal acquisition and analysis. For these reasons, one can envisage a widespread of such technologies due to the mentioned advantages in conjunction with low cost, flexibility in fabrication, simple signal processing, biocompatibility, and biodegradability.